A Textual Criticism and Lexical Analysis of Isaiah 62 - Philip Suciadi Chia; Juanda Juanda (Jurnal Didaskalia, 2019)
This research presents a methodology and example of doing both a textual criticism and a word study or a lexical analysis of the Hebrew word. The textual external evidence strongly favors the consonantal text of reading one because all the ancient versions support it. The internal evidence, though it is not as strong as external evidence, has endorsements from its context and appearances of that word in Hebrew Bible. In Isaiah 62:1, the best understanding of יד ִּפַל is not from literal sense but rather symbolic. The context of the usage of this term is God will restore Zion, particularly in her salvation, which is symbolized as a torch that burns. It means that Yahweh will make glorious Zion’s deliverance like a torch so that all nations, including their kings, will be witnesses of Zion’s restoration.